Collaboration Between Parents and Teachers in Building a Learning Ecosystem in the Digital Era - Hubbil Khair (Nurul Jadid University, 2025)
The rapid growth of digital technology in the 21st century has transformed education into a more flexible, interactive, and sustainable learning ecosystem. This study explores the collaboration between parents and teachers in supporting digital-based learning in madrasahs, the challenges faced, and the strategies to overcome them. Using a qualitative case study design, data were collected through interviews, observations, and documentation involving teachers, parents, and school administrators.The findings show that teachers serve as learning designers, facilitators, evaluators, and role models, while parents act as companions, motivators, and supervisors who ensure the responsible use of technology. Challenges include limited parental digital literacy, unequal access to devices and internet, and ineffective communication.Solutions involve digital literacy training, the use of accessible communication platforms, and the development of collaborative programs between schools and parents. The study concludes that the success of digital learning depends not only on technology but also on human collaboration based on trust and shared responsibility, offering both theoretical and practical contributions to educational transformation in the digital era.